Rigiditas dan Fleksibilitas Diskursus Fiqih Wanita Hizbut Tahrir - Chaidaroh, Umi (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2017)
Many women in modern times take part in public spaces. Moreover, women are also involved with Islamic movements which are often associated as fundamentalist movements such as Hizbut Tahrir (HT). In Indonesia, HT has a wing of women?s organization called the Muslimah Hizbut Tahrir Indonesia (MHTI). Women?s activists play pivotal role in the public space to help HT achieve its goals. Fundamentalist women who work in the public sphere seem to contradict with the growing assumption asserting that Islamic fundamentalist movements are often associated with the magnitude of oppression against women. It has been, however, seems to be a paradox. Considering the aforement-ioned argument, it is important to examine the thoughts concerning women?s jurisprudence of HT. Using compara-tive approach this study focuses on written literature as the main source. The results of the study prove that the thought concerning women?s jurisprudence of HT tends to be rigid. Interestingly, however, the study also finds that within particular cases the jurisprudence shows its flexibility, but it is even can be called liberal.